(untitled) (Faridpur Medical College Journal, 2012)
Giant fibroadenomas are benign tumors, but their rapid growth and large size together with their rarity may determine difficulties in the clinical approach. The authors present 2 cases of giant juvenile fibroadenoma of the breast in girls aged 14 and 16 years, and the respective diagnostic workup and conservative surgical treatment. The diagnosis was made on fine needle aspiration cytology which was confirmed on histopathology. These tumours are almost always benign and should be treated with breast conserving surgery. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10298 Faridpur Med. Coll. J. 2012;7(1): 42-45